KAJIAN TERHADAP ISU PEMBELIAN TANAH WAKAF MENERUSI MEKANISME WAKAF TUNAI DI NEGERI SELANGOR: A Study on Issues in Waqf Land Purchasing Through Mechanism of Cash Waqf in Selangor - Mustapa, Siti Salwani; Wahid, Hairunnizam; Ibrahim, Mohd Faisol (Jurnal Syariah, 2023)
The practice of waqf is vital in the development of the entire Muslim community. The waqf system at the Perbadanan Wakaf Selangor (PWS) has expanded in various ways or methods to include cash waqf, general waqf and special waqf, therefore providing Muslims with the opportunity to perform worship in a collective manner in order to enhance the Muslim community’s socio-economic status. This study was conducted to understand the concept of land purchase using cash waqf in the state of Selangor. The objective of this study is to ascertain the current status of waqf for the purchase of land through the cash waqf mechanism, along with issues in implementing it. This study used both the library study method and a field study to collect qualitative data. Data for this study was also obtained from semi-structural interviews with PWS officers and those involved in the management of waqf property. The findings show that waqf for land purchase within the state of Selangor has achieved its objective, despite challenges faced. The constraints regarding the waqf system are that the waqf fund collection had not achieved its target in addition to the short contract durations, which had caused the development of the planned waqf property to not run smoothly. Several recommendations and policy implications are suggested to ease future purchases of land through the cash waqf scheme so that it will become a valuable asset used for Muslims’ economic development.